Factors influencing organizational performance: a dynamic capabilities (DCS) practiced by hotel industry in Melaka post pandemic era - Johari, Shazali; Isa, Siti Suriawati; Ramlan, Mohd Aswad; Sukor, Salfarina (Faculty of Human Ecology, UPM, 2024)
In Malaysia, tourism arrival statistics indicated a high reduction trend from 26.10 million in the year 2019 to 4.33 million in the year 2020. This trend continues decreasing to only 0.13 million in the year 2021 and caused a big drop in receipt to 0.24 billion. This situation indicates that it has been critical for our tourism and hotel industry in ensuring the survival of the operations, especially due to the COVID-19 pandemic. Therefore, this research has closed the gap by providing new dynamic capabilities (DCs) dimensions to be applied by the other hotels to face the uncertainty of market shifts such as pandemics or economic downturns, renew competencies, and adapt faster to any changes in the internal or external environment. Quantitative approach used in this study involved 86 respondents from 65 hotels which are a hotels member of Malaysian Association of Hotels (MAH) in Melaka. Data collected through an online survey. Method to analyze data are descriptive and multiple linear regression using IBM SPSS Statistics Version 25. Instruments adopted from previous scholars through validated questionnaires have been executed. The findings of the research revealed that Market Orientation and Knowledge management dimensions were revealed to be the strong factors that influenced the organizational performance of the hotels in Melaka. Taking everything into account, this research has contributed to the body of knowledge specifically by exploring and exploiting the new dynamic capabilities that would help to unlock the potential of the internal or external resources of the hotel’s organization. This study proved that the DCs were effective, and previous researchers have been highlighting the significance of DCs as a factor in influencing the organizational performance of the hotels industry. Nevertheless, choosing the best and most suitable DCs for the industry will influence the direction of success, especially when dealing with internal challenges, customers, competitors, and market fluctuations.